A New Technology for Isolation and Manipulation of Single Protoplasts of Apomictic Reproductive Cells in Panicum maximum - Lanzhuang Chen; Yoshiko Nishimura; Chenti Xu (Microbiology and Biotechnology Research: An Overview Vol. 1, 2025)
Apomixis is a mode of reproduction in which only the mother’s genes are transmitted from generation to generation. If this trait can be exploited, it can be expected to have an economic effect that exceeds that of the "Green Revolution". Apomixis is divided into three types from a breeding point of view, that is, adventitious embryogenesis, apospory and diplospory. The latter two belong to the gametophyte type. The reproductive mode of the gametophyte type of apomixis is basically divided into two parts. The first is the formation of an embryo sac at the 2n level; the second is that the egg cell of the embryo sac automatically develops into an embryo without fertilization. Guinea grass (Panicum maximum Jacq.) belonging to apospory was used and this study was carried out at Minami Kyushu University located in 31-degree north latitude of Japan. To do the molecular analysis of the mechanism of aposporous embryo sac initial cell (AIC) appearance, as the first step, we attempted to establish the system of isolating and manipulating single cells containing AIC using different methods in P. maximum. At first, single protoplasts were isolated from the ovaries staged in different developmental stages using different pre-treatments and different concentrations of enzyme solutions on ovaries; Based on this, the single protoplasts containing AIC were manipulated with ultra particle electronic syringe picopipet (UPESP) machine set onto microscope. The ovary of facultatively apomictic guinea grass (Panicum maximum) was used as a material in this study for single protoplast isolation. The ovaries were classified and collected from young buds and flowers staged in different developmental stages, according to the colors of stigma and the ovary length. Then, the ovaries were pre-treated with a needle into different shapes, and treated with different kinds of enzyme solution with different concentrations of mannitol to increase the efficiency of protoplast isolation. In final, the single protoplasts containing AIC isolated from different stages of ovaries were manipulated by handle control. The ovaries in different stages before AIC appearance, AIC appearance, and AIC-derived embryo sac formation were collected successfully and respectively, indicating that the stigma colors and length of ovaries are proportionate to stages of ovary maturity. And single protoplasts containing AIC were isolated from the ovaries staged in white to yellow color. 2) The ovaries were flooded in an enzyme solution and were pre-treated with a needle in 4 types, that is, (1) Cut in the micropylar end; (2) Cut in chalazal end; (3) Cut in the middle part; (4) after 1hr of (3) treatment, cut in micropylar end. As a result, the efficiency of protoplast isolation of (3) and (4) was 1-2 hrs shorter than that of (1) and (2). 12%, 11%, 10% and 9% were proper enzyme concentrations for obtaining perfect shingle protoplasts from the ovaries with white, yellow, peach and purple colors, respectively. 3) The single protoplasts containing AIC were collected and manipulated with UPESP in the performance of controlled aspiration and spit. This topic, in molecular analysis of the mechanism of AIC appearance of view, is relevant and promising, the key points were to isolate AIC single protoplasts from apomictic guinea grass using different methods, and then to establish the method of controlling a single protoplast using UPESP machine. The findings contribute to broader research on isolating and manipulation of reproductive cells, offering a useful tool for molecular analysis of AIC, and providing important information for clarification of apomixis reproductive mode which has potential implications for breeding strategies aimed at fixing F1 hybrid crops.